Influence of Monowave and Polywave LED Unites on G-Aenial Resin Composites' Polymerization: An In Vitro Study - Azadeh Ghaemi; Milad Molayi; Rayan Chaharmahali (Wolters Kluwer Medknow Publications, 2022)
Objectives: Trimethylbenzoyldiphenylphosphine oxide and phenylpropanedione photoinitiator components in resin composites have been used widely due to their white color. However, it seems that there are some limitations in the required polymerization initiator wavelength. This study aimed to evaluate the polywave and monowave light-activating devices (LEDs) on polymerization and shrinkage strain of two dental composites with different photoinitiator systems. Methods: In this experimental study, 24 samples were prepared in two groups, including G-Aenial A2 and bleach composites. Each group was divided into two subgroups: one cured by monowave LED unit and the other by polywave device. Then shrinkage strain of samples was evaluated using bonded disk technique. Results: Results showed the shrinkage strain of A2 and bleach composites using PW device was significantly greater than MW device. In addition, the A2 composite shrinkage action polymerized with MW device was significantly lower than shrinkage action of A2 and bleach composite using PW machine. Conclusion: The findings of this study revealed that polywave LEDs were more beneficial for the polymerization of resin composites.